Structify-Net: Random Graph generation with controlled size and customized structure - Cazabet, Remy; Citraro, Salvatore; Rossetti, Giulio (Peer Community Journal)

(untitled)
Network structure is often considered one of the most important features of a network, and various models exist to generate graphs having one of the most studied types of structures, such as blocks/communities or spatial structures. In this article, we introduce a framework for the generation of random graphs with a controlled size —number of nodes, edges— and a customizable structure, beyond blocks and spatial ones, based on node-pair rank and a tunable probability function allowing to control the amount of randomness. We introduce a structure zoo —a collection of original network structures— and conduct experiments on the small-world properties of networks generated by those structures. Finally, we introduce an implementation as a Python library named Structify-net.